CARBON MOLECULAR SIEVE MEMBRANE (CMSM) PERFORMANCE TUNING BY DUAL TEMPERATURE SECONDARY OXYGEN DOPING (DTSOD) - SINGH, RACHANA; KOROS, WILLIAM JOHN (2014)
The various embodiments of the disclosure relate generally to carbon molecular sieve membranes (CMSM) and their associated fabrication processes, and more particularly to CMSM that maintain high gas selectivities without losing productivity. Methods for enriching a mixture of gases in one gas via the use of the CMS membranes, and gas enrichment devices using the same, are also disclosed. Les divers modes de réalisation de la description concernent de manière générale des membranes de tamis moléculaire de carbone (CMSM) et leurs procédés de fabrication associés, et plus particulièrement une CMSM qui maintient de hautes sélectivités pour les gaz, sans perte de productivité. L'invention concerne également des procédés d'enrichissement en un gaz d'un mélange de gaz par l'utilisation d'une membrane CMS, et des dispositifs d'enrichissement en gaz les employant.